Reproductive Tract Infection In A Village Area Of Bangladesh - Khanam, Tanvin; Islam, Md Rafiqul; Sultana, Shamrin; Yesmin, Laila (KYAMC Journal, 2017)
Objective: To asses the incidence of reproductive tract infection among the married women in the reproductive age group living in the rural area of Bangladesh. Study design: Retrospective study Method: Hospital based study done for a period of six month January 2013 to june 2013. Only married women suffering from reproductive tract infection were included. Result: Out of 1288 female patient attended for treatment in OPD, 582 (46.47%) were found affected by RTI. Women of age between 15-35 years were mostly affected (85%). Abnormal vaginal discharge (100%) and itching were the most common symptoms. The disease was more common among the illiterate women (72%) and in low socio-economic group (58%). KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 642-644